Cross-cultural socialization under conditions of distant learning - Sheina, L. O.; Grashchenkova, V. V. (Соціально-гуманітарна науково-творча майстерня "Новий курс", 2020)
The work explores the situation with socialisation in higher school during the period of coronavirus lockdown. The problem of socialisation under such conditions is discussed. A way to provide cross-cultural socialisation is proposed.
Keywords: distant learning; cross-cultural socialisation; coronavirus; social disadaptation; social medium